Adverse Perinatal Outcomes: Their Association with Maternal Anemia : Perinatal Outcomes with Maternal Anemia - Aziz, Amna; Parveen, Shahida; Khan, Bushra; Sultana, Hajra; Akhtar, Asma; Raza, Kanwal (Pakistan Journal of Health Sciences, 2025)
The incidence of anemia during the third trimester of pregnancy correlates with a heightened risk of negative postnatal outcomes. Objective: To access the relationship between hemoglobin levels in laboring women and perinatal outcome. Methods: A prospective cohort study was done at Department of Obstetrics and Gynecology, Nishtar Hospital, Multan from September 2020 to December 2021 using non-probability purposive sampling technique. A total of 135 anemic pregnant women (Group A) fulfilling inclusion and exclusion criteria was recruited for the study from labour room plus 135 non-anemic women were also recruited as control group (Group B). The data was recorded and explored. Results: 135 anemic laboring pregnant ladies were taken in this study having mean age 25.63 ± 4.53 years (range; 19-37 years) and 85.2% had ages less than 30 years. Cesarean section deliveries were noted to be in 50.4% in group A (anemic women) versus 48.1% in group B (non-anemic women). Preterm birth was noted to be 29.6% in group A versus 6.7% in group B. Small for gestational age was 53.3% in group A versus 12.6% in group B. Low birth weight was 54.8% in group A versus 16.3% in group B. Still birth was 7.4% only in anemic women while it was not observed in control group. Conclusions: The results of this study supported strong relationship of low haemoglobin in mothers with untoward perinatal outcome; growth retarded babies, preterm, Low birth weight and cesarean section rate. Strong media awareness campaigns should be launched for awareness for iron supplementation among targeted population.